Формування імовірнісних характеристик економічної стійкості транспортно-логістичної системи - Бажан, Л.І. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Mathematical model of probability characteristics of economic sustainability of transport and logistics system based on the analysis of functioning of internal and external environment wherein a risk of system development determines effectiveness of final result is described.